Effectiveness of Secondary Prophylaxis with Benzathine Penicillin G in Preventing Recurrent Acute rheumatic fever and rheumatic heart disease in Brazilian Children: A Randomized Controlled Trial - Sophia Lucille Rodriguez; Lucia Fernandez (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: (ARF) and its sequela, (RHD), remain significant public health concerns in developing countries. Secondary prophylaxis with Benzathine Penicillin G (BPG) is the cornerstone of preventing recurrent ARF and progression of RHD. This study aimed to evaluate the effectiveness of BPG in preventing recurrent ARF and RHD in Brazilian children. Methods: A randomized controlled trial was conducted in a tertiary care hospital in Brazil. Children aged 5-15 years with a history of ARF and/or RHD were enrolled and randomly assigned to receive either BPG injections every 28 days or standard care (no BPG) for two years. The primary outcome was the incidence of recurrent ARF episodes. Secondary outcomes included the development of new or worsening RHD, echocardiographic parameters, and adverse events related to BPG. Results: A total of 200 children were enrolled (BPG group = 100, standard care group = 100). The median follow-up duration was 24 months. The incidence of recurrent ARF was significantly lower in the BPG group compared to the standard care group (4% vs. 18%, p < 0.001). The BPG group also demonstrated a reduced risk of developing new or worsening RHD (8% vs. 22%, p = 0.003). Echocardiographic parameters showed improvement in the BPG group, with a significant decrease in left atrial diameter and mitral regurgitation severity. Adverse events related to BPG were mild and infrequent. Conclusion: Secondary prophylaxis with BPG is highly effective in preventing recurrent ARF and RHD in Brazilian children. It should be considered a standard of care for all children with a history of ARF and/or RHD in endemic regions.